Influence of the New Media on the Watchdog Role of the Press in Nigeria - Agbo, Benedict Obiora; Chukwuma, Okechukwu (European Scientific Journal, ESJ, 2017)
Section 22 of Nigeriaâ€™s 1999 constitution indicates that the watchdog role is a constitutional duty of the press to ensure that government is responsible and accountable to the people. However, one major approach deployed by the press to enforce this crucial watchdog role is through investigative journalism. Investigative journalism provides a very potent platform for the press to unravel what is known as â€œfacts behind the factsâ€ particularly in governance. More so, the press is no doubt a beneficiary of the advantages of the new media. The rapidity and ubiquity of the new media is now very visible in journalism practice. The question however is, what is the impact of the new media in the enforcement of the watchdog role of the press? Consequent upon the above question, the researchers assert that the new media have fundamentally aided the execution of the watchdog function of the press. This was premised on the fact that the press now utilise the new media to add depth and context to the coverage of events and issues. The new media now provide wider platforms for not just the press but also the citizens to hold government accountable. With the new media, both the citizens and media professionals now hold government at all levels accountable based on their activities. The new media are now massively used to oppose and criticize government policies and programmes as well as expose government misdeeds such as bribery and corruption with a view to engendering improved government performance.